The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3389/fmars.2019.00099
|View full text |Cite
|
Sign up to set email alerts
|

Chesapeake Bay Inorganic Carbon: Spatial Distribution and Seasonal Variability

Abstract: Few estuaries have inorganic carbon datasets with sufficient spatial and temporal coverage for identifying acidification baselines, seasonal cycles and trends. The Chesapeake Bay, though one of the most well-studied estuarine systems in the world, is no exception. To date, there have only been observational studies of inorganic carbon distribution and flux in lower bay sub-estuaries. Here, we address this knowledge gap with results from the first complete observational study of inorganic carbon along the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 61 publications
(93 reference statements)
11
54
0
Order By: Relevance
“…Early studies suggested conservative behavior of alkalinity in the Patuxent (Brust & Newcombe, ) and Susquehanna (Carpenter et al, ) River Estuaries and the possibility of a sink in the James River Estuary (Wong, ). More recent studies suggest alkalinity sinks in the tidal fresh and oligohaline portions of the Susquehanna (Brodeur et al, ; Cai et al, ) and Potomac (Cerco et al, ) River Estuaries and sources (due to sulfate reduction) in the York River Estuary (Raymond et al, ), which are in broad agreement with our findings. Brodeur et al () suggested that the alkalinity sink in the upper mainstem bay was due to SAV in the Susquehanna Flats, although these authors found the mainstem bay as a whole to be a weak source on average, with significant seasonal fluctuations.…”
Section: Discussionsupporting
confidence: 93%
“…Early studies suggested conservative behavior of alkalinity in the Patuxent (Brust & Newcombe, ) and Susquehanna (Carpenter et al, ) River Estuaries and the possibility of a sink in the James River Estuary (Wong, ). More recent studies suggest alkalinity sinks in the tidal fresh and oligohaline portions of the Susquehanna (Brodeur et al, ; Cai et al, ) and Potomac (Cerco et al, ) River Estuaries and sources (due to sulfate reduction) in the York River Estuary (Raymond et al, ), which are in broad agreement with our findings. Brodeur et al () suggested that the alkalinity sink in the upper mainstem bay was due to SAV in the Susquehanna Flats, although these authors found the mainstem bay as a whole to be a weak source on average, with significant seasonal fluctuations.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study in the CB by Brodeur et al () observed latitudinal gradients in DIC and TA throughout the mainstem that are similar to our findings. We find good agreement with respect to the seasonal ranges in DIC and TA in the midbay (corresponding most closely R2 in this analysis) and lower bay (corresponding to R3W and R3E) with the observations of Brodeur et al () in both the mixed layer and below. The pH comparison is complicated by inconsistency in units, but we note that our observations are in good agreement with respect to overall seasonality, with decreased pH with depth and distance from the Bay mouth.…”
Section: Discussionsupporting
confidence: 92%
“…Here we present new observations spanning four seasons (Autumn 2016 to Summer 2017) to diagnose the spatiotemporal variability of the CO 2 system in the main stem of the CB, the largest estuary in the continental United States. This study builds on a growing body of work focused on the seasonality of the CO 2 system in the region (e.g., Brodeur et al, ; Shadwick, Friedrichs, et al, ; Shen, Testa, Li, et al, ). New shipboard observations are used to partition the seasonality of DIC into physical and biological drivers.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that the broad patterns in CO 2 system changes from one season to the next are captured by sampling with monthly or sparser resolution (see also Brodeur et al, ); however, attribution of the drivers of those changes to particular physical and/or biological processes is more robust with higher‐frequency observations. Furthermore, the discrete seasonal sampling does not allow the air‐sea CO 2 flux to be captured appropriately.…”
Section: Discussionmentioning
confidence: 98%
“…Investigations of the role of continental shelves in the uptake of atmospheric CO 2 have resulted in a broad classification of estuaries as net sources of CO 2 to the atmosphere and sources of inorganic and organic carbon to the continental shelves and coastal oceans (Borges et al, ; Cai et al, ; Chen & Borges, ; Flecha et al, ; Frankignoulle et al, ; Jiang et al, ). Sustained measurements of the CO 2 system and quantification of carbon fluxes in nearshore environments have increased in recent years (Brodeur et al, ; Joesoef et al, ; Shadwick et al, ; Signorini et al, ; Vandemark et al, ), and regional budgets have been developed (Herrmann et al, ; Laruelle et al, ; Najjar et al, ).…”
Section: Discussionmentioning
confidence: 99%